The Entrepreneur in "Transformation Cinema": Representing the Economic Changes of the 1990s in Poland, Czech Republic, and Slovakia. Issue 2 (May 2022) - Pehe, Veronika
This article analyses how economic change after 1989 was perceived and rooted in society through cultural representations, specifically in the film production of Poland and Czechoslovakia (and later the Czech Republic and Slovakia). The starting premise of this investigation is that popular commercial films, alongside the media and discourse of politicians and other key actors of the systemic transformation, also informed ideas about the free market circulating in the public sphere. Filmmakers, faced with the new realities brought about initially by the gradual liberalization of the economy in the late 1980s and later the systemic change of the economic transformation in both countries, immediately turned to capturing and fictionalizing the changes surrounding them. They presented audiences with role models of what it means to be a capitalist, but also tales of warning. This article investigates the "transformation cinema" of the 1990s, focusing on the figure of the entrepreneur and private enterprise. It examines how filmmakers searched for a visual language to critique or affirm the new social order, but also continued to work with inherited modes from the late socialist era. The article asserts that while the economic expectations conveyed through cinema focused largely on structuring the imagination of a new middle class in Poland, Czech(oslovak) cinema adopted a more sceptical outlook, suggesting that the promises of the free market were not available to "ordinary" working people.